Learners’ engagement in learning English via Youtube - Setiawati Setiawati; Muhammad Babaroza; Yanti Anggraini; Ika Purnama Sari (Pioneer: Journal of Language and Literature, 2025)
The learners of MA Hubbulwathan Duri were diligently clicking and commenting on videos, yet they often failed to take notes or practice the material being taught. Learners were entertained (due to engaging audiovisuals), but this enjoyment does not always translate into a deep understanding of English concepts. Some learners struggled to filter out linguistically accurate content among the abundance of available videos. This research aimed to find out learners’ engagement in English learning via YouTube. This research used a survey research design. The data analysis technique used was descriptive. The population of this research was the tenth grade of MA Hubbulwathan Duri. A census study was used as the sampling technique in this research. The sample consisted of 29 respondents, and the research instrument was questionnaires. The findings revealed that learners’ engagement in learning English via YouTube at MA Hubbulwathan Duri was categorized as High across all measured dimensions. YouTube can capture learners’ focus and mental attention. YouTube successfully encouraged learners to move beyond the stage of simply ‘hearing’ (input) to the stage of ‘trying to produce’ (output). The learners were working hard to connect what they already know with new information from YouTube. YouTube serves as a powerful media for English language learning.